Improving The Students’ English Ability by Using PowerPoint Presentation - Swantika, Ika; Harissandi, Refin; Anwar, Rossya Diva (English Language Teaching Prima Journal (ELT), 2023)
This research was done to investigate how PowerPoint presentation technique improves students’ speaking ability. Researchers used a qualitative method which is pre-experimental research design by applying pre-test and post-test based on the indicators of speaking skill, namely: Material, Manner, Vocabulary, and Pronunciation. The data obtained were categorized and analyzed based on several related theories. Regarding the result, it was found that the students shown a positive result by implementing PowerPoint presentation. Student perceives that it helps them to evaluate their ability to speak English, increasing motivation, as well as allowing them to think critically in the use of language. Although several aspects must be developed such as student pronunciation. This finding indicates that PowerPoint presentations are useful for improving students speaking skills